P-189 YI Vedolizumab Drug Levels During Maintenance Therapy in Inflammatory Bowel Disease Patients. (February 2017) - Koduru, Pramoda; Morrill, Amanda; Abraham, Bincy
Abstract : Background: Therapeutic drug monitoring (TDM) can help manage inflammatory bowel disease (IBD) patients by assisting clinicians in optimizing efficacy of drug and minimizing potential toxicity. TDM has been commercially available for anti-tumor necrosis factor (TNF) agents with several studies showing that adequate trough levels correlate well with clinical remission and mucosal healing. Vedolizumab (VDZ) is a gut-specific monoclonal antibody to α4β7 integrin which binds to intestinal mucosal addressin cell adhesion molecule 1 (MAdCAM-1) and mediates leucocyte trafficking to gut. Little is known on the influence of VDZ drug levels and its antibodies in the management of IBD patients. We present our experience in use of TDM in IBD patients on VDZ maintenance therapy with clinically active disease. Methods: In this retrospective chart review, we analyzed all IBD patients in our center that were treated with VDZ on maintenance dosing and underwent TDM through the first commercially available testing of VDZ drug levels and antibodies (Miraca Life Sciences). TDM was obtained reactively, during maintenance therapy, either due to primary non-response or secondary loss of response based on clinical symptoms as measured by Harvey-Bradshaw Index (HBI) or Ulcerative Colitis Disease Activity Index (UCDAI). Data regarding patient demographics, IBD type, concomitant medications, and prior use of biologics was collected. Management decisions were made on combination of drug levels, and if available, endoscopic findings. Results: A total of 8 patients (7 females) with average age of 40.5 ± 12.4 years (mean ± SD) were included in the study. There are 4 patients with ulcerative colitis (pancolitis [3], left sided colitis [1]) and 4 with Crohn's disease (ileocolonic disease [4]) and all of them are bio-experienced patients. Three patients were on immunomodulators (methotrexate [2] and 6-mercaptopurine [1]) and 1 patient on mesalamine. The average HBI was 6.5 ± 1.7 and UCDAI score was 7.5 ± 4.9. Drug interval was 8 weeks for 6 patients, 6 weeks for 1 patient and 4 weeks for 1 patient. Mean trough drug level was noted to be 17.4 ± 6.3. No patients had anti-drug antibodies. Three patients had mucosal healing on an interim endoscopy although there was no correlation with the drug levels (21.1, 13.9, and 15.4). Dosing interval was changed to 4 weeks in 4 patients and re-induction was recommended for 1 patient who was already at 4 weeks interval. No changes were made to dosing interval for 2 patients who had mucosal healing noted on endoscopy with drug levels at 13.9 and 15.4 respectively. Conclusions: Rosario et al reported that UC patients who participated in GEMINI I trial with higher VDZ trough concentrations during the induction phase had lower endoscopic sub-scores and achieved mucosal healing. No published data exists on the use of TDM for VDZ in IBD patients during maintenance phase. Our pilot group of IBD patients undergoing testing shows that drug monitoring for VDZ impacts clinical decision making in IBD patients. Larger studies need to be done with VDZ to determine ideal maintenance drug levels needed to maintain clinical and endoscopic remission.